Effect of neutral electrolyzed water (NEW) on Salmonella Typhimurium, Enteropathogenic Escherichia coli (EPEC) and Staphylococcus aureus - Dowidar, Maryam S.; Homouda, Seham N.; Abd El-Tawab, Ashraf A. (Journal of Advanced Veterinary Research, 2024)
In this study, Neutral electrolyzed water (NEW) bactericidal efficacy and inactivating capacity as a promising novel antimicrobial agent, green sanitizer and natural alternative to conventional decontamination techniques as chemical disinfectants was evaluated by using NEW with free available chlorine (FAC) at concentrations of 7.5 ppm (NEW 1%), 24 ppm (NEW 12%) and 49 ppm (NEW 25%) against food-borne related microorganisms and their biofilms. Our Results revealed that by 10 min of exposure to the sanitizer (NEW) with different concentrations, changes to the bacterial count, bacterial cell morphology, biofilms were evaluated by plate counting, minimum inhibitory concentration method (MIC), Transmission Electron microscope (TEM) examination for the isolated Salmonella Typhimurium, Enteropathogenic E. coli (EPEC), and S. aureus, respectively. Beside, modulation of bacterial gene expression by real time Polymerase Chain Reaction screening (RT-PCR) for methicillin- resistant gene (mecA) and Enterotoxin gene (seb) of S. aureus. It was shown from the results that Salmonella Typhimurium highest reduction percentage achieved was 99.9% after 10 min exposure to 12% and 25% NEW concentrations, while EPEC and S. aureus highest reduction percentages achieved were 99.8%, and 99.95% after 10 min exposure to 25% NEW concentration, respectively. The lowest reduction was detected by 59.5% for S. aureus treated with NEW 1% for 5 min. While MIC for NEW 25% was 12.25 ppm for EPEC and 24.5 ppm for each of Salmonella Typhimurium and S. aureus. TEM photos revealed that NEW has achieved a broad-spectrum bactericidal activity by causing changes and destruction in cell envelope and cytoplasm of all strains. RT-PCR showed downregulation of enterotoxin (seb) and resistant genes (mecA) of S. aureus. In conclusion, the study demonstrated that NEW as a green sanitizer is significant in reduction and elimination of the most food-borne bacterial contamination.